The ASEM Education Process: Implications for higher education internationalization in Malaysia - Munusamy, M.Miandy; Hashim, Azirah (AEI Insights, 2021)
The education process of the Asia-Europe Meeting (ASEM) has played an important role in higher education internationalisation since the establishment of ASEM in Bangkok, Thailand in 1996. The ASEM Education Process (AEP) consists of 53 ASEM partners and more than 15 ASEM education stakeholders who meet regularly for discussions on policies and reform measures. There are four priority areas and two transversal themes introduced in the AEP for policy direction and strategy implementation in the field of higher education. Malaysia has participated in the AEP since 2008 and has led and organised various initiatives and meetings on the internationalisation of higher education and global recognition. This study aims to explore the implications of the AEP for the process of internationalisation of higher education in Malaysia. A qualitative study with semi-structured interviews was conducted with fifteen senior officers of the Ministry of Higher Education, Malaysia and five Malaysian research universities. The data were analysed by employing the Qualitative Data Analysis software, the Nvivo version 11, to identify themes and categories. The findings reveal that the AEP can play a major role in internationalising Malaysian higher education through effective networking and strategic alliances. The four priority areas of the AEP has provided opportunities for Malaysia to work closely with European and Asian counterparts in the field of higher education. The findings can assist the Malaysian higher education stakeholder to participate actively in the inter-regional organisation to learn and share best practices and to formulate and revise policies on higher education internationalisation.